Utilisation of High Molecular Weight and Ultra-High Molecular Weight Hyaluronan in Management of Glioblastoma - Alex-Adrian Salagean; Cezara-Anca-Denisa Moldovan; Mark Slevin (Gels)
HA (hyaluronan) has been considered in recent years as a naturally occurring modifiable gel-like scaffold that has the capability to absorb and release drugs over an extended period of time making it suitable as a potential chemotherapeutic delivery agent. Considering the limited treatment options available in the treatment of glioblastoma, in this review, we discuss the novel utilisation of ultra-high molecular weight HA—originally identified as a mechanism for maintaining longevity in the naked mole-rat—as both a protective and extracellular matrix-optimizing colloidal scaffold, and a means to deliver therapy in resected brain tumours. The unique properties of this unique form of HA cross-linked gel indicate potential future use in the prevention and treatment of both proliferative-based and inflammation-driven disease.